STUDY ON THE COMBATEMENT OF STRESS BY KINETOTHERAPY MEANS - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
I have chosen to deepen this theme because I believe that the world in which we live is becoming stronger and a serious problem in all points of view. Any activity carried out in everyday life causes stress which leads to the disease of the population and an increase in mortality rates. Stress can cause different conditions, such as: gastritis (inflammation of the stomach wall), ulcer (wound on the stomach), HTA-Hypertension, Diabetes, arteriosclerosis (fat on the walls of the arteries), AVC (stroke), Hyperthyroidism (increase in thyroid volume), nervous system can cause Alzheimer's (memory loss), sensory disorders: visual and clogged ear disorders, dermatological conditions (acne, itching, etc)[4].